Anosognosia for memory in dementia with Lewy bodies compared with Alzheimer's disease. (25th February 2021) - Calil, Victor; Silveira de Souza, Andrea; Sudo, Felipe Kenji; Santiago‐Bravo, Gustavo; Assunção, Naima; Drummond, Claudia; Rodrigues, Fernanda; Soares, Rejane; Oliveira, Natalia; Teldeschi, Alina; Bernardes, Gabriel; Lima, Gabriel; et al.
Abstract: Objectives: Anosognosia is the inability to recognize one's own symptoms. Although dementia with Lewy bodies (DLB) is the second most common degenerative dementia, there is little evidence of memory deficit awareness in this condition. The objectives of this research were to compare anosognosia between individuals with DLB and dementia due to Alzheimer's disease (AD) and to evaluate whether medial temporal atrophy, a marker of AD pathology, could help to explain different rates of anosognosia in DLB and dementia due to AD. Methods/Design: This is a cross‐sectional study that took place at the Memory Clinic of D'Or Institute for Research and Education (IDOR). Twenty individuals with DLB and 20 with dementia due to AD were included in this study. We assessed anosognosia for memory using an index derived from subjective memory complaints (using the Memory Complaint Questionnaire) and from the performance in memory neuropsychological testing (Rey Auditory Verbal Learning Test). Thirty‐one participants also underwent brain Magnetic Resonance Imaging to evaluate hippocampal atrophy with a visual scale (MTA‐score [medial temporal atrophy score]). Results: There was no significant difference between groups regarding age, years of education, sex or time of disease. Individuals with DLB had a higher index of anosognosia than dementia due to AD (2.92 and 1.87; p  = 0.024), meaning worse awareness of memory deficits. MTA‐score was slightly higher in dementia due to AD than in DLB, albeit without statistical significance. Conclusion: Our study was the first to demonstrate that anosognosia for memory is worse in DLB than in dementia due to AD. This finding supports the hypothesis that anosognosia in DLB is a heterogeneous phenomenon. Key Points: In our sample, anosognosia for memory was worse in dementia with Lewy bodies (DLB) than in dementia due to Alzheimer's disease (AD) Anosognosia for memory is a heterogeneous phenomenon in DLB Medial Temporal Atrophy, measured by the medial temporal atrophy score, was not useful to support the hypothesis that AD pathology burden is responsible for anosognosia for memory in DLB